2018
DOI: 10.1042/cs20180057
|View full text |Cite
|
Sign up to set email alerts
|

The neutrophil-mobilizing cytokine interleukin-26 in the airways of long-term tobacco smokers

Abstract: Long-term tobacco smokers with chronic obstructive pulmonary disease (COPD) or chronic bronchitis display an excessive accumulation of neutrophils in the airways; an inflammation that responds poorly to established therapy. Thus, there is a need to identify new molecular targets for the development of effective therapy. Here, we hypothesized that the neutrophil-mobilizing cytokine interleukin (IL)-26 (IL-26) is involved in airway inflammation amongst long-term tobacco smokers with or without COPD, chronic bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 47 publications
(79 reference statements)
5
25
0
Order By: Relevance
“…Different studies have reported that IL-26 activates innate (27) and adaptive lymphoid cells (28) as well as myeloid cells (29) and plasmacytoid dendritic cells (pDC) (18). However, with the exception of alveolar macrophages (25) and non-stimulated neutrophils (26, 30), immune cells do not express IL-20R1, suggesting the existence of alternative IL-26-signaling pathway(s) in the activation of IL-20R1-negative cells.…”
Section: The Il-26 Protein and Signaling Elementsmentioning
confidence: 99%
“…Different studies have reported that IL-26 activates innate (27) and adaptive lymphoid cells (28) as well as myeloid cells (29) and plasmacytoid dendritic cells (pDC) (18). However, with the exception of alveolar macrophages (25) and non-stimulated neutrophils (26, 30), immune cells do not express IL-20R1, suggesting the existence of alternative IL-26-signaling pathway(s) in the activation of IL-20R1-negative cells.…”
Section: The Il-26 Protein and Signaling Elementsmentioning
confidence: 99%
“…18 Moreover, IL-26 enhances the chemotactic response of human neutrophils to bacterial and inflammatory stimuli. 12 In this way, Che et al 19 found increased extracellular IL-26 protein in the airways of long-term smokers in vivo. Recombinant human IL-26 increased gene expression of NF-κB and pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 90%
“…Recombinant human IL-26 increased gene expression of NF-κB and pro-inflammatory cytokines. 19 Innate lymphoid cells (ILCs) are part of the innate immune system. 20 ILC3s, the most implicated in asthma can play a role in the recruitment of neutrophils to the lung via the cytokine IL-17A eventually leading to neutrophilic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Another candidate for neutrophil-targeted therapy may be IL-26, which is a neutrophil mobilizing cytokine that is increased in BALF of COPD patients and long term smokers [136]. In addition, an alternative treatment strategy may be the use of AZD7986, a competitive and reversible inhibitor of dipeptidyl peptidase 1 (DPP1), which was shown to inhibit whole blood NE activity in healthy volunteers after once-daily dosing for 21-28 days with no serious side effects [137].…”
Section: Granulocyte-targeted Therapies For Copdmentioning
confidence: 99%